PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA: Studi Kasus Pada Sektor Manufaktur - Dura, Justita (LP2M Institut Teknologi dan Bisnis Asia Malang, 2017)
This study aims to determine the effect of profitability, solvency and size of the company to the audit report lag in manufacturing companies listed in Indonesia Stock Exchange 2010-2013. The samples used as many as 105 companies with purposive sampling technique. The analysis technique used is multiple linear regression analysis. The results showed that (1) the profitability affect audit report lag indicates that companies that get a big profit tends to make the process shorter than audit firms experienced a small profit. (2) the liquidity affect audit report lag, (3) the solvency effect indicates that the high amount of debt of the company will lead the audit process is relatively long, and (4) the size of the company does affect indicating that a large or small amount of assets owned by the company does affect the length or in short the process of preparing the financial statements of the company.